Analisis Pengaruh Budaya terhadap Keefektifan Komunikasi Bisnis dalam Organisasi - Mirza Mahendra Siregar; Rismayanti Bintang; Amaliyah Mutiara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to discuss culture and communication and their influence on the effectiveness of business communication. First, it is important to study internally how communication affects the organization. And will lead to how organizations do business with people in different cultures. Earlier. Data collection techniques by examining research journals or scientific articles, books, documents, or other information related to the research title. In the business world, many studies have shown that communication has a significant influence on the growth of a company, because in any business, communication is very important. The existence of communication between employees and company owners or with what is called organizational culture is no less important than communication, which we can see that has a very large impact on development. Communication practices are shaped by cultural characteristics. Therefore, the two go hand in hand working together. Culture has a strong influence on communication. This means that culture has an impact on various aspects of our lives. Culture also influences interpersonal communication. Merriam-Webster (2018)